Mario Acosta: capstone - Acosta, Mario, artist (Colorado State University. Libraries, 2019)
The artist's statement: Communication in the media is here to stay, whether you wish to say where you were for lunch, or if you want to invite others for lunch. In any case, I strive to tackle those, and many other design challenges. If a design problem arises, and it allows me to continue to help the world, our home, you will see me spending countless hours working from idea to product. Currently I'm focusing on how media will continue to evolve thanks to new technologies. Before me we focused on newspapers, magazines, online, and now, I see augmented reality as the future for consumer design. I see us, humans, continuing to transition to a digital space, and while the physicality of print will be missed, it will give our world a break from our trash.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, images of works and videos.
Video has no spoken word.